Online versus Offline in Purchase Channel Decision for Fresh Food from the Perspective of Cooking Inconvenience - 김지열; 이철 (인터넷전자상거래연구, 2018)
Although the online market is growing fast, sales of fresh food are growing slowly compared to other products. Certain fresh foods sold well in online stores, but many other foods appear less popular. For understanding the difference, this study investigated whether any peculiar characteristics of fresh food could be the difference between offline and online sales. In this study, 428 individual participants were recruited and each participant completed 1712 questionnaires in response to an online survey questionnaire on four fresh foods. The results of this study showed that the inconvenience of after cooking fresh food products had a negative effect on intention to purchase offline and did not affect the intention to purchase online. Therefore, fresh food products that have an unpleasant smell and are difficult in terms of cleaning and supplementary work may be suitable for sale in the online market.
Keywords: Food Product; Fresh food; Intention to Purchase; Online Shopping; Offline Shopping